Histomorphometric Analysis and Markers of Endometrial Receptivity Embryonic Implantation in Women With Polycystic Ovary Syndrome During the Treatment With Progesterone. (July 2014) - Lopes, Ione Maria Ribeiro Soares; Maganhin, Carla Cristina; Oliveira-Filho, Ricardo Martins; Simões, Ricardo Santos; Simões, Manuel Jesus; Iwata, Margareth Chiharu; Baracat, Edmund Chada; Soares, José Maria
Literature data indicate that the infertility in women with polycystic ovary syndrome (PCOS) is not only attributed to anovulation but also to endometrial dysfunction. Endometrial biopsies were performed in the proliferative and secretory phases of women with normal cycle and in women with PCOS before and after oral treatment with micronized progesterone. After the treatment, the endometrium of the women with PCOS exhibited a lower number of glands and thicker luminal epithelium compared to the normal women in the secretory phase. In addition, the PCOS group exhibited reduced integrin and MECA-79 immunoexpression during the secretory phase. The expression of E-cadherin was higher in the PCOS and the expression of intercellular adhesion molecule 1 was lower in PCOS, during the secretory and proliferative phases, respectively. Also, there is a negative correlation with MECA-79 and integrin expression and body mass index. Conventional doses of progesterone may not be enough to correct the changes of endometrial histomorphology and the receptive markers of PCOS-bearing women. The obesity may be a factor that interferes with this response.